2021
DOI: 10.3390/biomedicines9081042
|View full text |Cite
|
Sign up to set email alerts
|

177Lu-PSMA Radioligand Therapy Is Favorable as Third-Line Treatment of Patients with Metastatic Castration-Resistant Prostate Cancer. A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials

Abstract: In this systematic review and network meta-analysis (NMA), we aimed to assess the benefits and harms of third-line (L3) treatments in randomized controlled trials (RCTs) of patients with metastatic castration-resistant prostate cancer (mCRPC). Two reviewers searched for publications from 1 January 2006 to 30 June 2021. The review analyzed seven RCTs that included 3958 patients and eight treatments. Treatment with prostate-specific membrane antigen (PSMA)-based radioligand therapy (PRLT) resulted in a 1.3-times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 81 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…The differentiation between 68 Ga-PSMA positive and negative scans was not statistically significant (mean PSA: 8.39 ± 23 vs. 4.22 ± 5.99 ng/mL, median PSA: 2.71 vs. 1.40 ng/mL, n.s.). The detection efficacy in the patient group Ga-RP was 75% (12) for PSA levels of 0.2 to <0.5 ng/mL, 86.7% (13), 76.9% (10), 94.4% (17), and 88.9% (24) for PSA levels of 0.5 to <1, 1 to < 2, 2 to < 5, and ≥5 ng/mL, respectively (p = 0.108) (Table 6). All of the 28 BCR patients in the F-RT patient group showed a positive 18 F-PSMA scan (100%) (mean PSA 9.10 ± 10.16 ng/mL) with 15 patients with PSA levels of 2 to <5 ng/mL and 13 patients with PSA values of ≥5 ng/mL, respectively.…”
Section: Positivity Rate With [ 68 Ga]ga-psma-11 Pet/ct In Patients W...mentioning
confidence: 98%
See 1 more Smart Citation
“…The differentiation between 68 Ga-PSMA positive and negative scans was not statistically significant (mean PSA: 8.39 ± 23 vs. 4.22 ± 5.99 ng/mL, median PSA: 2.71 vs. 1.40 ng/mL, n.s.). The detection efficacy in the patient group Ga-RP was 75% (12) for PSA levels of 0.2 to <0.5 ng/mL, 86.7% (13), 76.9% (10), 94.4% (17), and 88.9% (24) for PSA levels of 0.5 to <1, 1 to < 2, 2 to < 5, and ≥5 ng/mL, respectively (p = 0.108) (Table 6). All of the 28 BCR patients in the F-RT patient group showed a positive 18 F-PSMA scan (100%) (mean PSA 9.10 ± 10.16 ng/mL) with 15 patients with PSA levels of 2 to <5 ng/mL and 13 patients with PSA values of ≥5 ng/mL, respectively.…”
Section: Positivity Rate With [ 68 Ga]ga-psma-11 Pet/ct In Patients W...mentioning
confidence: 98%
“…Thus, PSMA provides an optimal target for diagnosis and therapy of PC lesions. Several PSMA ligands for labeling with 68 Gallium ( 68 Ga) and 18 Fluor ( 18 F) have been developed in recent years and nuclear medicine physicians continue to investigate imaging with [ 68 Ga]Ga-PSMA-11 PET/CT ( 68 Ga-PSMA) and with [ 18 F]PSMA-1007 PET/CT ( 18 F-PSMA) [9][10][11][12]. Compared to 68 Garadiolabeled tracers, the 18 F radionuclides offer advantages in terms of physical properties such as longer half-life and lower positron range with a higher image resolution [9].…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of randomized controlled trials in patients with mCRPC, the benefits and harms of eight third-line (L3) treatments for prostate cancer were evaluated. Compared with treatment with abiraterone, enzalutamide, mitoxantrone or cabazitaxel, PSMA PRLT resulted in a higher rate of PSA decline and a 1.1-fold increase in PFS (30). Although it was a preliminary study, it had shown the great potential of targeted radionuclide therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Von Eyben et al conducted two extensive reviews of the literature to compare, in the absence of phase III study data available at that time, the efficacy of PRLT to third-line systemic treatment of metastatic castration-resistant prostate cancer (mCRPC). 17,18 A PSA50 is observed in 44% of patients with PRLT compared to 22% for third-line systemic therapy ( p = 0.0002, t test). In addition, the objective response rate was greater for PRLT compared to third-line systemic therapy (28% versus 16%, p = 0.004); as was median survival, albeit not significantly so (14 months versus 12 months, p = 0.32).…”
Section: Part 1: Psma Radioligand Therapy (Prlt)mentioning
confidence: 97%